Study on Basic Characteristics of CuAlBe Shape Memory Alloy - Canbay, C. Aksu; Karaduman, O.; Unlu, N.; Ozkul, I. (Springer, 2021)
In this work, the CuAlBe shape memory alloy (SMA) with a new composition of 77.05Cu-22.02Al-0.93Be (at.%) detected by the EDS test was fabricated in a vacuum arc melter under a pure argon atmosphere. At the beginning, the high-purity (%99.9) elements of Cu, Al, and Be powders were mixed and the mixture (similar to 10 g) was formed as pellets by pressure. By melting the pellets in arc melter, the as-cast ingot alloy was obtained. Then, the ingot alloy was cut into small pieces (similar to 30-50 mg) and then all of these samples were all homogenized in the beta-phase region (at 900 degrees C for 1 h) and immediately submerged in traditional iced-brine water to form beta 1' martensite phase in the alloy which results from such fast cooling by suppressing the formation of hypoeutectoid precipitations (alpha and gamma 2). Then, to uncover and evaluate the existence of martensite structure and the characteristics of shape memory alloy properties of the alloy, the specimens were tested by calorimetric and structural measurements. The results of thermal heating/cooling cycles of the alloy were obtained from differential scanning calorimetry (DSC) measurements that were taken twice at 5 degrees C/min of heating/cooling rate under constant argon gas flow (100 ml/min) and by using liquid nitrogen cooling support to reach lower temperatures than room temperature. The DSC thermograms of the alloy revealed the characteristic martensitic transformation peaks that occurred endothermic by heating and exothermic by cooling at moderate temperatures ranging between 19 and 66 degrees C, regarded as evidence for the presence of shape memory effect property in the alloy. Important thermodynamical parameters such as transformation temperatures, hysteresis gap, and entropy and enthalpy change amounts for these back and forward martensitic phase transition peaks were determined directly by using data of DSC peak analyses and by calculation. Differential thermal analysis (DTA) measurement that was taken from room temperature to 900 degrees C at a heating/cooling rate of 25 degrees C/min displayed a high-temperature behavior of the alloy as compatible with the common behavior of Cu-Al SMAs. The X-ray test of the alloy conducted at room conditions showed sharp diffraction peaks and their matching crystal planes which indicate the existence of beta 1 ' martensite phase in the alloy and its high single-like crystallinity i.e. its large Debye-Scherrer sub-micrometer crystallite size. Besides, theoretical forecasting about the existence and volumetric dominance of martensite phases was deduced from the calculated value of e/a (average conduction electron concentration per atom) parameter of the alloy. Furthermore, the mechanical Vickers microhardness tests that were performed at room temperature and under 100-gf load applied for 10 s revealed the high ductility and softness features of the alloy. Considering all the results, the highly ductile CuAlBe alloy with new composition owing shape memory alloy properties and intermediate working temperatures can be useful in various kinds of research and applications in which Cu-based SMAs are exploited.
Keywords: Ductile CuAlBe SMA; Martensite; Differential calorimetry; XRD; Vickers microhardness test